Personal beliefs as a worldview factor of psychological well-being - Gruzinova, Ksenia (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2020)
The article is devoted to researching the connections between aspects of psychological well-being and personal beliefs in the context of limitations in social functioning during a pandemic. The survey had conducted in the form of a written group survey of respondents. In the research, the following research methods were provided: R. Yanov-Bulman Basic Belief Scale; methods of diagnosing the individual’s subjective well-being [11]. The results of the research were analyzed by using statistical processing methods.The peculiarities of the connections between the aspects of well-being and personal beliefs were revealed. The presence of a person’s belief in the benevolence and justice of the world is mostly due to the experience of emotional and existential well-being. The belief in the goodness of people and the value of one’s own «self» in the structure of personal beliefs is associated mainly with a higher level of ego-well-being. It was proved that the general level of psychological well-being depends on beliefs: in commitment to the world, justice of the world, the kindness of people, and values of «self». The study made it possible to establish that the features of various aspects of psychological well-being and beliefs in the period of social constraints caused by the pandemic COVID-19. Higher indicators of existential-activity well-being and ego-well-being had the persons who noted the absence of deterioration of the social functioning during the pandemic. Also, among persons who did not experience a deterioration in social functioning during the quarantine period, higher rates of belief in the world’s justice and the value of one’s own «self» were found.Thus, the role of basic beliefs as a worldview factor of well-being was proved, the peculiarities of their interdependence during the pandemic were studied. Empirical evidence has established the relationship between beliefs in the commitment and justice of the world, people’s kindness, and the value of the «self» with various aspects of well-being.
Keywords: worldview; aspects of well-being; pandemic; benevolence of world; justice of world; world-attitude